Informal Carers Training: In-group Social Learning as an Effective Method for Quality Care Empowerment - Ramovš, Jože; Ramovš, Ana; Svetelšek, Ajda (Frontiers in Sociology, 2019)
In this article, a method of group social learning used for informal carers training is presented. This method was developed by Jože Ramovš and his team at the Anton Trstenjak Institute of Gerontology and Intergenerational Relations primary for the fields of holistic health prevention and ageing; later on, special attention has been given to its development for training of informal carers as the latter often carry the most significant part of the long-term care burden. In the first part of the article, the need for such a method is discussed through a review of current international demographic and long-term care situations. In the second part, a novel method for the training of informal carers is introduced. Finally, the results of the evaluation analysis of 453 persons who participated in the training are presented and compared with the results of the nationally representative study. The results show that the method of group social learning has a great potential for quality care empowerment of informal carers as well as for holistic development of intergenerational solidarity in the modern age. Furthermore, they open new possibilities for research and present directions for further development and implementation of the described method within this important field.